Gender performance and attitudes toward mathematics in BUSCEP students at Universidade Eduardo Mondlane - Cassy, Bhangy (My University, 1997)
After Mozambique became independent from Portugal, the main aim of the government policy towards education was to create equity of opportunity to enter the formal education system for different social, gender and age groups. However, females are still under-represented in higher education particularly in courses which require an extensive mathematical background. Thus, the purpose of this study was, to explore possible gender differences in performance and attitudes toward mathematics among 1996 BUSCEP students at Universidade Eduardo Mondlane. Those students were tested on several affective and cognitive variables, using a questionnaire and tests. The results suggested that gender performance and attitudes towards mathematics tend to be similar, and the inequalities found, were more evident in the participation in mathematics related careers. These findings emphasise the need to further examine the interrelationships between gender and career choices which should be conducted with students from the secondary school.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 1997.
Keywords: Mathematical ability--Sex differences; Mathematics--Study and teaching (Higher)--Mozambique; Women in mathematics--Mozambique; Educational equalization--Mozambique